BIOACCUMULATION OF ARSENIC IN THE FRESHWATER FISH LABEO ROHITA (HAM.) - K. PAZHANISAMY; M. VASANTHY; N. INDRA (The Bioscan, 2006)
Bioaccumulation of arsenic in the fish- Labeo rohita, was investigated after exposure to two sub lethal concentration of arsenic trioxide (1/10th - 0.27 ppm and 1/3rd - 0.91 ppm of the 96 h LC50) for 7th, 14th, 21st & 28th days. The highest / maximum level of accumulation of arsenic was seen in the liver whereas the lowest level of arsenic had been accumulated in the muscle tissues at the end of 28 days of exposure period. It is clear that arsenic has been accumulated primarily in the liver tissues of L. rohita exposed to sublethel concentration of arsenic. The present investigation indi- cates that the rate of accumulation of arsenic was found to be dose and time dependent.